Strategy for the treatment of plunging ranula. Case report (Research, Society and Development, 2020)
Ranula is defined as a pseudocyst originated from the leakage of mucinoid fluid of the sublingual gland, often associated with trauma or obstruction of the gland duct. Clinically, characterized by bluish and translucent color on the floor of the mouth and can be classified as an intraoral or plunging ranula. Diagnosis includes detailed clinical and imaging exams combined with histopathological findings. Therapeutic approaches can be applied to treat this lesion, such as marsupialization, excision of the ranula with or without the sublingual gland and excision of the ranula together the sublingual and submandibular gland. The aim of this paper was to report a case of plunging ranula, treated by excision followed by marsupialization of the cystic lesion, after one year of follow-up with recurrence. We conclude that a less invasive treatment may not present the best strategy for the treatment of plunging ranula, due to the greater chances of recurrence.